TINGKAT KEPUASAN PASIEN JAMKESMAS TERHADAP PELAYANAN RAWAT INAP DI RUMAH SAKIT UMUM PROVINSI NUSA TENGGARA BARAT - Kirtiasih, Ida Ayu; Syamsun, Arfi; Affarah, Wahyu Sulistya (Jurnal Kedokteran, 2014)
Background: Jamkesmas is a health insurance which is used since 2008-2013 for the poor of Indonesian. The last implementation of Jamkesmas insurance is still facing problems for instance membership, finance and services. The patients satisfaction is one of an evaluation of the services have been done, so it can be used as a benchmark to continue the new health insurance program which is called JKN (Jaminan Kesehatan Nasional) especially for the government provincial west nusa tenggara barat (RSUP NTB) hospital. Methods: The type of research is a descriptive study categorical with cross-sectional design. Statistical analysis used univariate analysis. Results: Respondents of female showed more satisfied compared of men.The most satisfied through the ward unit services showed by group of age over 50. Every ward needs to fix of services based on reability variable. The most satisfaction showed by assurance variable and the lowest is reliabillity variable . Conclusion: The satisfaction level of patients Jamkesmas through ward unit services at government provincial West Nusa Tenggara hospital reached 74% base on average 5 variables. Keywords: Satisfaction, Services, Patients, Jamkesmas, Hospitalization, Hospital.